The Didactic Aspects Of Politeness Strategies In Online Written Interactions Of E-learning - Beddiaf, Abderrazak; Beddiaf, Abdelkader (جامعة الوادي - University of Eloued, 2022)
Virtual teaching/learning provides space for interaction. As a result, the characteristics of the exchanges must respond to and correspond to certain communication constraints, whose politeness strategies make it possible to boost group interaction in a collaborative context. Indeed, through this article, we aim to analyze the use and the value of politeness strategies through their frequency and their manifestation supposed to guarantee a dynamic and the harmony of the situations of interactions and collaboration in the action. to teach and learn online.
articl
Keywords: Online teaching (e-Learning) ; interaction ; politeness strategies ; speech acts ; ICTs